Traditional Islamic Education and Global Challenges: A Qur'anic and Hadith-Based Normative Framework - Muhammad Annas Firdaus (JF Publisher, 2026)
Contemporary global education increasingly prioritizes measurable competencies and academic performance, often at the expense of moral formation, values development, and social responsibility. This tendency has intensified concerns regarding the ethical and humanistic dimensions of education in an era shaped by rapid technological change and globalization. This study examines how traditional Islamic educational institutions, specifically kuttab, pesantren, and madrasah diniyah, respond to twenty-first-century educational challenges through the normative guidance of the Qur'an and Hadith. Employing a qualitative library research design, this study analyzed primary data consisting of selected Qur'anic verses and authenticated Hadith traditions alongside secondary data drawn from Scopus-indexed academic literature published between 2021 and 2026. Data were examined through thematic and normative-conceptual analysis, with source triangulation applied to verify the consistency of findings across textual, prophetic, and scholarly sources. The findings indicate that core Islamic values, including tawhid, akhlaq, justice, amanah, and social responsibility, derived from the Qur'an and Hadith, align substantively with global educational agendas concerned with character development and global citizenship. A three-layer conceptual model is proposed, integrating revelation as normative foundation, values-based education as pedagogical core, and principled engagement with modernity as adaptive strategy, governed by the principle of wasatiyyah. Traditional Islamic educational institutions demonstrate both adaptability and normative coherence, offering a sustainable and integrity-based model of values education for addressing contemporary global educational challenges.